(untitled) (PerCursos, 2025)
The article proposes to discuss - based on the collection and investigation of administrative microdata provided by SISMIGRA - the legal mechanisms regularly used by international migrants and refugees as legal protection for documented stay in Brazilian territory, with an emphasis on the context and migratory routes that have had the highest influx into Santa Catarina in the last two decades. It also seeks to understand the possible dynamics of permanence and circulation of these individuals, as well as the impacts of these migratory flows on the state. Legal protection is the support offered by a legal system, based on various provisions that provide support, protection, guarantee of rights, obligations, and standards of conduct for individuals within a territory. In the case of migrants in situations of international displacement, there are several challenges to activating these legal protections and to their full integration into the host society.